'The More Sport the Merrier, Say We': Sport in Ireland during the Great Famine. (December 2018) - Griffin, Brian
Scholars have made considerable progress in recent years in researching the history of sport in Ireland, yet there are still important areas that have not received scholarly attention. One of these is the topic of sport during the Great Famine. A close perusal of contemporary newspapers reveals that large numbers of Irish people, from all social groups, continued to enjoy sports, either as participants or as spectators, during the Famine years. Horse races, especially steeplechases, were universally popular, with many meets attracting attendances that numbered in the thousands. Other popular sports included fox hunting, stag hunting, greyhound coursing, sailing, cricket and cockfighting. This article illustrates the widespread popularity of sport in Ireland in this period, based mainly on a reading of newspaper accounts, and discusses why the subject of sport does not feature in folk or popular memory of the Famine.